Analisis Keterlaksanaan Pembelajaran Fisika Berbasis Inkuiri Terbimbing Dipadu Advance Organizer di SMA - Mahesti Kusdiastuti; Gunawan Gunawan; Ahmad Harjono (Indonesian Publication Center, 2021)
This study aimed to analyze the implementation fidelity of guided inquiry-based physics learning integrated with an advance organizer during field testing in senior high schools. As part of the development phase in a 4D research model, this descriptive quantitative study involved tenth-grade students across three public senior high schools in Mataram, Indonesia. Data regarding learning implementation were collected over four instructional sessions using structured observation sheets administered independently by two observers at each school. The observation scores were analyzed descriptively to determine average implementation percentages and inter-observer reliability. The findings revealed a consistent upward trend in learning implementation across all three target schools. Initial sessions (Meetings I and II) demonstrated a